Β‐cell dysfunction and insulin resistance in relation to pre‐diabetes and diabetes among adults in north‐western Tanzania: a cross‐sectional study. Issue 4 (27th January 2021) - PrayGod, George; Filteau, Suzanne; Range, Nyagosya; Kitilya, Brenda; Kavishe, Bazil B.; Ramaiya, Kaushik; Jeremiah, Kidola; Rehman, Andrea M.; Changalucha, John; Olsen, Mette Frahm; Andersen, Aase Bengaard; Friis, Henrik; et al.
Abstract: Objective: Studies on phenotypes of diabetes in Africa are inconsistent. We assessed the role of β‐cell dysfunction and insulin resistance on pre‐diabetes and diabetes. Methods: We included 1890 participants with mean age of 40.6 (SD11.9) years in a cross‐sectional study among male and female adults in Tanzania during 2016 to 2017. Data on C‐reactive protein (CRP), alpha‐acid glycoprotein (AGP), HIV, oral glucose tolerance test (OGTT), body composition and insulin were collected. Insulinogenic index and HOMA‐IR were used to derive an overall marker of β‐cell dysfunction and insulin resistance which was categorised as follows: normal β‐cell function and insulin sensitivity, isolated β‐cell dysfunction, isolated insulin resistance, and combined β‐cell dysfunction and insulin resistance. Pre‐diabetes and diabetes were defined as 2‐hour OGTT glucose between 7.8–11.0 and ≥ 11.1 mmol/L, respectively. Multinomial regression assessed the association of β‐cell dysfunction and insulin resistance with outcome measures. Results: β‐cell dysfunction, insulin resistance, and combined β‐cell dysfunction and insulin resistance were associated with higher pre‐diabetes risk. Similarly, isolated β‐cell dysfunction (adjusted relative risk ratio (aRRR) 4.8 (95% confidence interval (CI) 2.5, 9.0), isolated insulin resistance (aRRR 3.2 (95% CI 1.5, 6.9), and combined β‐cell dysfunction and insulin resistance (aRRR 35.9 (95% CI 17.2, 75.2) were associated with higher diabetes risk. CRP, AGP and HIV were associated with higher diabetes risk, but fat mass was not. 31%, 10% and 33% of diabetes cases were attributed to β‐cell dysfunction, insulin resistance, and combined β‐cell dysfunction and insulin resistance, respectively. Conclusions: β‐cell dysfunction seemed to explain most of diabetes cases compared to insulin resistance in this population. Cohort studies on evolution of diabetes in Africa are needed to confirm these results.